Application of metabolomics approach to investigate the flavor substance differences between triploid and diploid oysters (Crassostrea angulata) - Chen, Duo; Zheng, Zewen; Zhou, Ziquan; Song, Yuxin; Chen, Zhi; Lin, Gang; Xue, Ting (Frontiers in Marine Science, 2024)
Oysters, particularly Portuguese oyster (Crassostrea angulata), are highly valued for their nutritional and flavor qualities, making them important in global aquaculture. Triploid oysters have gained attention for maintaining higher meat quality year-round compared to diploids, but there is limited research on how ploidy affects their biochemical and flavor profiles. This study uses a non-targeted metabolomics approach, including gas chromatography-mass spectrometry (GC-MS) and liquid chromatography-mass spectrometry (LC-MS), to investigate flavor substance differences between triploid and diploid C. angulata. A total of 13 volatile compounds were identified in diploid oysters, while 28 were found in triploids. Significant upregulation of inosine, guanosine, L-aspartic acid, and taurine in triploids contributes to their enhanced flavor profile. Additionally, triploids showed higher nicotinamide concentrations, while diploids had increased 25-hydroxycholesterol. These findings highlight the advantages of triploid oysters in aquaculture for improved flavor and nutrition, supporting their potential for year-round production.